2018
DOI: 10.7567/jjap.57.07le04
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ultrasonic effect on powder and application to radioactive sample compaction

Abstract: The effect of ultrasound on powder compaction was analyzed. The decreasing in the friction coefficient of the powder sample is derived theoretically. The compaction rate was improved by the ultrasound. We applied the effect to the compaction of environmental radioactive soil samples. From γ-ray spectroscopy analysis, more radionuclides could be detectable in the sample compacted with ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14] In a previous study, we suggested the theoretical model for analyzing the effect of ultrasound on powder compaction. 15) The decrease in the friction coefficient of the powder sample caused by ultrasound was confirmed theoretically and experimentally under constant static pressure. However, in that model, the change in static pressure was not taken into consideration, and the compacting effect could be different if the static pressure was changed.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14] In a previous study, we suggested the theoretical model for analyzing the effect of ultrasound on powder compaction. 15) The decrease in the friction coefficient of the powder sample caused by ultrasound was confirmed theoretically and experimentally under constant static pressure. However, in that model, the change in static pressure was not taken into consideration, and the compacting effect could be different if the static pressure was changed.…”
mentioning
confidence: 73%
“…Generally, the powder compaction is performed with ultrasonic vibration as well as high static pressure. Recently, we suggested a theoretical analysis of the ultrasonic effect on the powder compaction 4) . In this study, to analyze the improvement of compaction caused by ultrasonic vibration under various static pressure appling to the powder, the effective friction coefficient and sound speed of the powder are examined theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%